Is Firm Pricing State or Time Dependent? Evidence from U.S. Manufacturing - Midrigan, Virgiliu (The Review of Economics and Statistics, 2010)
If pricing is state dependent, firms are more likely to adjust whenever aggregate and idiosyncratic shocks reinforce each other and trigger desired price changes in the same direction. Using measures of technology shocks derived from production function estimates for four-digit U.S. manufacturing industries, I find that sectoral inflation rates are more sensitive to negative, as opposed to positive, technology disturbances in periods of higher economy-wide inflation, commodity price increases, and expansionary monetary policy shocks. I argue, using a state-dependent sticky price model that matches salient features of the U.S. microprice data, that these results suggest that pricing is state-dependent in U.S. manufacturing.